Hyperalgesia in an immobilized rat hindlimb: Effect of treadmill exercise using non-immobilized limbs. (1st January 2015) - Chuganji, Sayaka; Nakano, Jiro; Sekino, Yuki; Hamaue, Yohei; Sakamoto, Junya; Okita, Minoru
Highlights: Immobilization of limb induced mechanical hyperalgesia in rats. The hyperalgesia could be reduced by treadmill running during immobilization period. This effect might be based on an activation of descending pain modulatory system in the brain. Abstract: Cast immobilization of limbs causes hyperalgesia, which is a decline of the threshold of mechanical and thermal mechanical stimuli. The immobilization-induced hyperalgesia (IIH) can disturb rehabilitation and activities of daily living in patients with orthopedic disorders. However, it is unclear what therapeutic and preventive approaches can be used to alleviate IIH. Exercise that activates the descending pain modulatory system may be effective for IIH. The purpose of this study was to investigate the effects of treadmill exercise during the immobilization period, using the non-immobilized limbs, on IIH. Thirty-six 8-week-old Wistar rats were randomly divided into (1) control, (2) immobilization (Im), and (3) immobilization and treadmill exercise (Im + Ex) groups. In the Im and Im + Ex groups, the right ankle joints of each rat were immobilized in full plantar flexion with a plaster cast for an 8-week period. In the Im + Ex group, treadmill exercise (15 m/min, 30 min/day, 5 days/week) was administered during the immobilization period while the right hindlimb was kept immobilized. Mechanical hyperalgesia was measured using von Frey filaments every week. To investigate possible activation of the descending pain modulatory system, beta-endorphin expression levels in hypothalamus and midbrain periaqueductal gray were analyzed. Although IIH clearly occurred in the Im group, the hyperalgesia was partially but significantly reduced in the Im + Ex group. Beta-endorphin, which is one of the endogenous opioids, was selectively increased in the hypothalamus and midbrain periaqueductal gray of the Im + Ex group. Our data suggest that treadmill running using the non-immobilized limbs reduces the amount of hyperalgesia induced in the immobilized limb even if it is not freed. This ameliorating effect might be due to the descending pain modulatory system being activated by upregulation of beta-endorphin in the brain.